Romania : Staff Report for Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Romania has made significant progress in stabilization and reform. Executive Directors welcomed this development, and stressed the need to maintain monetary and fiscal policies, and accelerate structural reforms. They welcomed the fiscal strengthening and progress in bank restructuring and privatization. Nevertheless, they called for strict adherence to the macroeconomic policy targets and intensified efforts in the areas of bank reform and enterprise privatization, and considered that greater clarity in the framework and objectives of monetary policy would be helpful.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet